(untitled) (The Pakistan Development Review, 2007)
Over the last four decades world economy has experienced several wide swings in energy prices. These swings have very serious repercussions for countries of Asian, in general, and South Asian regions, in particular; the latter having tremendous economic potential. Rapidly growing economies like India, China and Pakistan will face serious energy crisis if they do not plan well for future needs. Energy is one of the most critical inputs to several variety of production function. And we have very limited ability to replace it by other means in the short run, without having serious setback to our GDP. Energy conservation is a topic that has been discussed over a long period of time. Energy conservation is not a local issue but a global one, affecting the strategic planning and policy making of the governments worldwide. Energy conservation is proving as a catalyst for globalisation and international trade of energy.